Experiências de violência urbana: o estudo do grupo como dispositivo de produção e socialização de estratégias de enfrentamento - Ferreira, Rogerio Santos [UNIFESP] (2014)
From the understanding that violence is an element of urban life that weakens the quality of life and health of the population in general form, the present study intended to verify the contributions of the group as intervention device, its potential and limitations. For this purpose, the case study method of the qualitative approach was used. As a technique for data collection open interviews were conducted in the form of experience narratives and observation participant with field journal records in the development of group experiences. Data interpretation was performed from the use of the technique of content analysis. The results show that the group provides the socialization of coping strategies when the topic is related to urban violence, it was observed that participants have acquired conduct characterized by empowerment face a urban violence experienced in their daily lives in the territory, realizing that they?re not alone in reality daily confrontation such perverse and shocking as the violence, contributing to the production and socialization of collective coping strategies.